Making more : how life begins - Roy, Katherine (Norton Young Readers, an imprint of W.W. Norton & Company, 2023)
"From fish to mammals and plants to insects, every organism on Earth must reproduce, and the survival of each species--and of life itself--depends on this and on the diversity it creates. In this groundbreaking book, Katherine Roy distills the science of reproduction into its simplest components: organisms must meet, merge their DNA, and grow new individuals; and she thoughtfully highlights the astonishing variety of this process with examples from across the natural world, from plants to insects to fish, birds, mammals, and more"--